Democratic Management and Professional and Technological Education (EPT): the Importance of Spaces for Student Participation in School Management at the Federal Institute of the North of Minas Gerais (IFNMG) (Research, Society and Development, 2024)
As provided for in the Federal Constitution of 1988 and ratified by the LDB, education is a right for all Brazilian citizens. Based on the educational objectives set out in the legislation, Paulo Freire's theory of liberating education and the project of an integral education, on which the teaching program of the Federal Institutes is based, this article is based on the proposal of an education aimed at critical formation of the student, in which the role of the school is to form autonomous subjects, capable of intervening in reality and not just adapting them for integration into the market. To carry out this study, qualitative documentary research was used on the existing documentation on the phenomenon under study. In this sense, the objective of this study is to highlight the relevance of spaces for student participation in school management at IFNMG for the implementation of democratic and participatory management at school.